1985
DOI: 10.1073/pnas.82.12.4142
|View full text |Cite
|
Sign up to set email alerts
|

In situ localization of DNA topoisomerase II, a major polypeptide component of the Drosophila nuclear matrix fraction.

Abstract: DNA topoisomerase II has been immunochemically identified on protein blots as a major polypeptide component of the Drosophila nuclear matrix-pore complexlamina fraction. Indirect immunofluorescence analyses of larval cryosections have confirmed the nuclear localization of topoisomerase II in situ. Although apparently excluded from the nucleolus, the topoisomerase protein is otherwise distributed throughout the interior of interphase nuclei. Similar immunocytochemical studies performed with permeabilized whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
177
0
4

Year Published

1987
1987
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(188 citation statements)
references
References 39 publications
7
177
0
4
Order By: Relevance
“…Previously described matrix attachment regions are generally A/T-rich and contain sequences identical or similar to the cleavage site of topoisomerase II, a major component of the nuclear matrix and chromosomal scaffold (Cockerill and Garrard, 1986;Berrios et al, 1985;Earnshaw et al, 1985;. By contrast, human telomeric repeats are G-rich and although topoisomerase II cleavage of telomeric repeats has not been tested, the repeat sequences do not conform the topoisomerase II consensus site (GTNA/TAC/TATTNATNNA/G).…”
Section: Discussionmentioning
confidence: 99%
“…Previously described matrix attachment regions are generally A/T-rich and contain sequences identical or similar to the cleavage site of topoisomerase II, a major component of the nuclear matrix and chromosomal scaffold (Cockerill and Garrard, 1986;Berrios et al, 1985;Earnshaw et al, 1985;. By contrast, human telomeric repeats are G-rich and although topoisomerase II cleavage of telomeric repeats has not been tested, the repeat sequences do not conform the topoisomerase II consensus site (GTNA/TAC/TATTNATNNA/G).…”
Section: Discussionmentioning
confidence: 99%
“…One of the best characterized components of the chromosomal scaffold is DNA topoisomerase 11 (topo 11) [4][5][6][7]. Besides its enzymatic activity that creates transient double-strand breaks in duplex DNA and passes DNA strands through one another, the protein has been shown to interact with the MAR and SAR elements [8].…”
Section: Introductionmentioning
confidence: 99%
“…255 meres containing highly condensed chromatin, while the lateral loops consist of decondensed, transcriptionally active chromatin covered with numerous nascent transcripts. Because lampbrush chromosome architecture resembles so closely the proposed organization of somatic interphase chromatin and mitotic chromosomes, it is tempting to speculate that the same molecular components might be involved in the maintenance of chromatin loops.One of the best characterized components of the chromosomal scaffold is DNA topoisomerase 11 (topo 11) [4][5][6][7]. Besides its enzymatic activity that creates transient double-strand breaks in duplex DNA and passes DNA strands through one another, the protein has been shown to interact with the MAR and SAR elements [8].…”
mentioning
confidence: 99%
“…By using the drug VM26, Rowe et al (38) have shown that topoisomerase II can interact in vivo near the 5' and 3' ends of the hsp70 heat shock gene. Immunofluorescence studies of interphase nuclei and polytene chromosomes of D. melanogaster show a broad distribution of topoisomerase II within the nuclei and chromosomes, respectively (3,25). In contrast, immunofluorescense studies of Drosophila polytene chromosomes have shown that topoisomerase I is restricted to a subset of loci, apparently being recruited to those that are transcriptionally active (15,43).…”
mentioning
confidence: 99%